2022
DOI: 10.3389/fonc.2022.803804
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Self-Controlled Study of Indocyanine Green, Radioisotope, and Methylene Blue for Combined Imaging of Axillary Sentinel Lymph Nodes in Breast Cancer

Abstract: PurposeThis self-controlled study aimed to clarify whether indocyanine green (ICG) could be an alternative tracer in the absence of radioisotope (RI) for combined imaging of axillary sentinel lymph node (SLN) in breast cancer.MethodsPrimary breast cancer, clinically axillary node-negative patients (n = 182) were prospectively enrolled from March 2015 to November 2020. ICG, methylene blue (MB), and RI were used to perform axillary sentinel lymph node biopsy (SLNB). The main observation index was the positivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…We concluded that the detection rate of SLNs with the ICG + MB group was significantly higher than that with MB alone (98.5% vs 91.5%). This finding is consistent with earlier research [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…We concluded that the detection rate of SLNs with the ICG + MB group was significantly higher than that with MB alone (98.5% vs 91.5%). This finding is consistent with earlier research [ 7 , 8 ].…”
Section: Discussionsupporting
confidence: 94%
“…The authors found that the IR of ICG is 95.4% in patients after primary systemic therapy, and 94.3% for primary SLNB [37]. This is in accordance with the study by Jin et al on the use of the triple ICG + RI + BD technique, that also included clinically node-negative patients as well as patients receiving NACT, and reported that the IRs were more than 98% and not significantly different between the two groups [51]. Another study by Papathemelis et al, a single-arm analysis on the use of dual ICG + RI method, included 104 patients, of whom 19 were in the post NACT setting, and reported an IR = 100% for the combined ICG + RI technique, with an FNR of 4.8% for RI in contrast to 0% for ICG.…”
Section: Icg As Slnb Tracer In the Post Nact Settingsupporting
confidence: 86%
“…Furthermore, Somashekhar et al who analyzed the data of 100 clinically node-negative breast cancer patients who received ICG + BD + RI guided SLNB, concluded that the detection rate of ICG was 96%, not significantly different than the IR = 94% for the dual BD + RI method. Another investigator who enrolled 182 clinically node-negative patients, as well as patients in the post NACT setting, to receive SLNB with all three tracers, found that the ICG + BD method yielded IR = 100%, not significantly different than the IR = 98.9% for the standard BD + RI technique [51].…”
Section: Studies Using Icg Ri and Bd As Slnb Tracersmentioning
confidence: 97%
“…A previous study has found that in SLNB using the dual-tracer method (combined MB and ICG) for breast cancer, all 19 metastatic SLNs were uorescent positive, but up to 8 lymph nodes were not stained by MB 19 . Another similar study has also reported 2 cases where only uorescent SLNs were found to be metastatic 20 . However, the extremely limited relevant data available has not been able to conclusively correlate the staining patterns of MB and ICG with metastatic status in SLNs.…”
Section: Discussionmentioning
confidence: 79%